2015
DOI: 10.1103/physrevstper.11.020117
|View full text |Cite
|
Sign up to set email alerts
|

Review of student difficulties in upper-level quantum mechanics

Abstract: Learning advanced physics, in general, is challenging not only due to the increased mathematical sophistication but also because one must continue to build on all of the prior knowledge acquired at the introductory and intermediate levels.In addition, learning quantum mechanics can be especially challenging because the paradigms of classical mechanics and quantum mechanics are very different. Here, we review research on student reasoning difficulties in learning upper-level quantum mechanics and research on st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
146
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 143 publications
(147 citation statements)
references
References 82 publications
1
146
0
Order By: Relevance
“…While this study focused on student understanding of probability distribution of measurement outcomes, future investigations will focus on other equally challenging topics in quantum mechanics and strategies to help students learn those concepts better. For example, students also have difficulties with topics such as possible outcomes of measurements, expectation values, and time development of quantum states and time dependence of expectation values [7]. Furthermore, in the study described here, we found that students had difficulties both with Dirac notation and position and momentum representations in the context of probability distributions for measurement outcomes.…”
Section: Summary and Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…While this study focused on student understanding of probability distribution of measurement outcomes, future investigations will focus on other equally challenging topics in quantum mechanics and strategies to help students learn those concepts better. For example, students also have difficulties with topics such as possible outcomes of measurements, expectation values, and time development of quantum states and time dependence of expectation values [7]. Furthermore, in the study described here, we found that students had difficulties both with Dirac notation and position and momentum representations in the context of probability distributions for measurement outcomes.…”
Section: Summary and Discussionmentioning
confidence: 78%
“…research has shown that students often think that the operator should appear in the expression for calculating probability of measuring a particular eigenvalue of the operator [6,7]. Some interviewed students who incorrectly claimed that the operator should appear in their expression for calculating probability made conceptual arguments claiming that, in quantum mechanics, an operator acting on a generic state must yield an eigenvalue of the corresponding operator.…”
Section: ˆ| ⟩| Previousmentioning
confidence: 99%
See 3 more Smart Citations